A Modern Technology Applied in Traditional Chinese Medicine: Progress and Future of the Nanotechnology in TCM. Issue 3 (4th September 2019) - Yan, Guojun; Wang, Yonglin; Han, Xinxin; Zhang, Qian; Xie, Hui; Chen, Jun; Ji, De; Mao, Chunqin; Lu, Tulin
The application of nanotechnology to traditional Chinese medicine (TCM) enabled the development of Chinese medicine in the international society. The pharmacodynamics of TCM is not only depending on its chemical constituents but also related to its physical state such as particle size. Indeed, there is some new pesticide effect that appeared when the medicine was being made into nanophase. The application of nanotechnology to TCM can expand the use of a range of Chinese medicinal materials. In this review, we introduce the concept of nanometer TCM. We also review the preparation methods, advantages, and development tendency of Nano-TCM; furthermore, we analyze the problems in the process of development of Nano-TCM and put forward varies possible solutions to solve this problems, thereby providing new thought for the development of Nano-TCM.